Rotator cuff retear after repair surgery: comparison between experienced and inexperienced surgeons - Jin-Young Park; Jae-Hyung Lee; Kyung-Soo Oh; Seok Won Chung; Yunseong Choi; Won-Yong Yoon; Dong-Wook Kim (Clinics in Shoulder and Elbow, 2021)
Background We hypothesized in this study that the characteristics of retear cases vary according to surgeon volume and that surgical outcomes differ between primary and revision arthroscopic rotator cuff repair (revisional ARCR). Methods Surgeons performing more than 12 rotator cuff repairs (RCRs) per year were defined as high-volume surgeons, and those performing fewer than 12 RCRs were considered low-volume surgeons. Of the 47 patients who underwent revisional ARCR at our clinic enrolled in this study, 21 cases were treated by high-volume surgeons and 26 cases by low-volume surgeons. In all cases, the interval between primary surgery and revisional ARCR, degree of “acromial scuffing,” number of anchors, RCR technique, retear pattern, fatty infiltration, retear size, operating time, and clinical outcome were recorded. Results During primary surgery, significantly more lateral anchors (p=0.004) were used, and the rate of use of the double-row repair technique was significantly higher (p<0.001) in the high- versus low-volume surgeon group. Moreover, the “cut-through pattern” was observed significantly more frequently among the cases treated by high- versus low-volume surgeons (p=0.008). The clinical outcomes after revisional ARCR were not different between the two groups. Conclusions Double-row repair during primary surgery and the cut-through pattern during revisional ARCR were more frequent in the high- versus low-volume surgeon groups. However, no differences in retear site or size, fatty infiltration grade, or outcomes were observed between the groups.